(untitled) (Gumilyov Journal of Pedagogy, 2026)
This article examines the main challenges encountered in teaching complex topics in high school biology. The research focuses on the sections of molecular biology, biochemistry, genetics, and coordination and regulation systems. The aim of the study is to identify the factors that hinder the understanding of these topics among students and teachers and to propose effective pedagogical approaches. Based on a mixed methods design, the findings revealed that the major difficulties include the abstract nature of the content, time constraints, insufficient laboratory equipment, and the complexity of textbook language. To address these issues, the study suggests using visual and interactive tools, expanding laboratory activities, and optimizing the curriculum. Furthermore, the use of modern technologies and multimedia resources has been shown to increase students’ engagement and improve learning effectiveness. The results highlight the need to enhance teachers’ professional competence, refine teaching strategies, and strengthen laboratory infrastructure. Practically, the study recommends increasing the proportion of laboratory and experimental lessons, applying active learning methods, and organizing the teaching process more efficiently. This research makes a valuable contribution to improving the quality of biology education and developing students’ scientific inquiry skills.rocess.